2015
DOI: 10.1353/cpr.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mentoring for Male Parolees: A CBPR Pilot Study

Abstract: This study demonstrated the feasibility and import of involving formerly incarcerated adults in the design, implementation, and testing of interventions intended to support their reintegration efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“… 75 78 The authors’ search also revealed a recently published pilot study that evaluated a peer support program for formerly incarcerated adults who transitioned back into the community that included investigations of craving among other varriables. 79 This population experiences high rates of substance use. One of the main objectives of this study was to assess program feasibility using a community-based participatory research approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 75 78 The authors’ search also revealed a recently published pilot study that evaluated a peer support program for formerly incarcerated adults who transitioned back into the community that included investigations of craving among other varriables. 79 This population experiences high rates of substance use. One of the main objectives of this study was to assess program feasibility using a community-based participatory research approach.…”
Section: Resultsmentioning
confidence: 99%
“… 69 Associated positive changes have also been demonstrated such as improvements in negative affect, social support perceptions, reductions in habitual craving, and feelings of guilt or shame. 69 , 79 All of these areas play important roles in one’s ability to achieve and sustain abstinence from substances. There were conflicting results from studies on whether or not quality-of-life improvements were associated with peer support groups being included in services.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used participant observation to contextual the experiences of health workers, while semi-structured interviews aimed to understand how the intervention empowered community health workers. An additional number of studies demonstrate pre-post quasi-experimental design and participatory approaches, to include Andersen et al (2015), Garney et al (2015), and Marlow et al (2015).…”
Section: Participatory Mixed Methods In Community Psychologymentioning
confidence: 99%
“…Especially for individuals with mental health and substance use disorders, peer programs have demonstrated effectiveness in improving their linkage and engagement with services (Bagnall et al 2015; Nyamathi et al 2015; Blodgett et al 2013). Although there is some evidence that peer programs may improve a variety of outcomes for the reentry population (Rowe et al 2007; Goldstein et al 2009; Marlow et al 2015), there are few published interventions focusing on veterans. To address this evidence gap, this paper describes how process mapping contributed to the design of a locally relevant peer-support intervention to assist veterans as they return to community settings after incarceration.…”
Section: Introductionmentioning
confidence: 99%